Species-specific foraminifera-bound nitrogen isotope and foraminiferal calcite oxygen and carbon isotope measurements from DSDP Site 516 in the South Atlantic over a glacial-interglacial cycle - Auderset, Alexandra; Smart, Sandi; Ryu, Yeongjun; Marconi, Dario; Ren, Haojia Abby; Heins, Lena; Vonhof, Hubert B; Schiebel, Ralf; Repschläger, Janne; Sigman, Daniel M; Haug, Gerald H; Martínez-García, Alfredo (PANGAEA, 2025)
This dataset contains species-specific foraminifera-bound nitrogen isotope (FB-δ15N) measurements from sediment core samples at Deep Sea Drilling Program Site 516, located in the subtropical South Atlantic gyre. Complementary species-specific carbon and oxygen stable isotope measurements were performed on foraminiferal shell carbonate, with additional size-specific carbon and oxygen isotope data collected for two samples. Isotopic measurements were conducted on the following foraminifera species: Trilobatus sacculifer, Globigerinoides ruber ruber, Globigerinoides ruber albus, Globorotalia truncatulinoides, Globigerinella siphonifera, and Globigerina bulloides. The data span a full glacial-interglacial cycle and provide species-specific isotopic variability to evaluate foraminifera-bound nitrogen isotopes as a new tool to determine paleo-photosymbiosis in planktic foraminifera.
Keywords: Foraminifera; Foraminifera-bound nitrogen isotopes; Glacial/Interglacial cycles; Oxygen and carbon stable isotopes; Pleistocene; symbiosis